POLICY IMPLEMENTATION OF ONE DATA INITIATIVE IN LOCAL GOVERNMENT: A CASE STUDY OF MEDAN CITY - Aulia Rahman; Tunggul Sihombing; Asima Yanty S. Siahaan (OPINI: Journal of Communication and Social Science, 2025)
This study aims to analyze the implementation of the One Data Policy in Medan City as a strategic effort to support the achievement of Indonesia’s Golden Vision 2045. The policy represents a public service innovation based on information technology, designed to establish an accurate, integrated, and transparent data system across regional government agencies. The research employs a descriptive qualitative approach using interviews, observations, and document analysis. Van Meter and Van Horn’s implementation theory serves as the analytical framework, encompassing six variables: policy standards and objectives, resources, characteristics of implementing agencies, disposition of implementers, inter-organizational communication, and external environment. The findings reveal that the standards and objectives have been outlined through Mayor Regulation No. 31 of 2021. However, the policy implementation faces several challenges, particularly in human resource capacity and inter-agency communication, which is hindered by sectoral egos. Despite support from the socio-political environment, the policy's impact on public service delivery remains suboptimal. The study recommends strengthening coordination, enhancing human resource capacity, and conducting regular evaluations to improve policy effectiveness in achieving long-term development goals.